PENGARUH VARIABEL EKONOMI MAKRO TERHADAP PENYALURAN PEMBIAYAAN MELALUI DANA PIHAK KETIGA SEBAGAI VARIABEL INTERVENING (Studi Kasus pada Bank Umum Syariah di Indonesia Tahun 2011–2015) - Mufidah, Lilik Zazilatul (Fakultas Ekonomi, UIN Maliki Malang, 2016)
Islamic banking development in Indonesia has been improving continuously. Islamic banking activityin fund distribution could not be separated from an influence of macro economic variable, because one of thefactors that influenced fund was macro economics outwardness of the company. The purpose of the researchwas to saw direct influence of macro variable toward fund distribution and indirect influence toward fundthrough intervening variable. Kind of the research method was quantitative, the research samples were sixgeneral Islamic Banking in Indonesia since 2011–2015 and was taken with purposive sampling. This researchused path analysis method. The result showed that interest income inflation and exchange rate did notinfluenced significantly toward third-parties fund. Whereas circulate money aggregation influenced significantlytoward third-parties fund. In the significant second test the result showed that inflation, interest income, andcirculate money aggregation influenced significantly toward fund distribution. In the third significant test, theresult showed that third-parties fund influenced significantly toward amount of fund distribution. Finally,from the results could be concluded that third-parties fund was only became intervening variable for thecirculate money aggregation, because the circulate money aggregation influenced third party fund and funddistribution.